A violação dos direitos humanos das vítimas e a ineficácia do processo penal nos delitos de homicídio - Scherner, Giovana César (2024)
This Master's dissertation has as its main focus is to highlight the victim of homicide in the face of deficient protection and the ineffectiveness of the criminal process. It aims to bring the victim's notoriety in the sense of changing his passive position in the criminal process, making him active, integrative and protagonist of the justice system. Constant delays in the trial of the defendant, bureaucracies in practice, in the process of the exercise of development of the criminal process, failures in the investigation, that is, a series of factors are considered obstacles to the consummation of the fair criminal process. The unreasonableness of the duration of the process may even lead to its perpetuation, without any result, even incurring in the statute of limitations of the crime. From this awareness of the rights of the victim of homicide, it is necessary to have a model of criminal procedure that transforms procedures and practices into institutional bases, capable of giving full voice and full protection to victims of homicide and their families. This analysis also encompasses the study of criminal procedural obligations, as well as identifying the failure to protect the victim. With the necessary effective search for concrete problems that violate the protection of homicide victims, this dissertation calls for a prompt and conclusive normative systematization. This systematization must obey respect for the human dignity of homicide victims, who occupy a place apart from the current model of Brazilian criminal procedure. Based on the principles of human rights, what is defended, above all, is the immanent right to the victim, as a human person. And, a criminal process will only be effective if this right is not violated. Thus, this dissertation raises the issue of the violation of the human rights of the victims in the face of the ineffectiveness of the criminal process, in the crimes of homicide. The victim must be considered as an integral part of the fair criminal process.